Polystyrene Microplastics Induce Insulin Resistance and Glucose Metabolism Disorders in Grass Carp (Ctenopharyngodon idellus) via the Gut Microbiome–Metabolism Axis - Fubin Zhang; Shuting Huang; Xueting Chen; Zhendong Qin; Li Lin (Fishes, 2025)
Polystyrene microplastic (PS-MP) particles disrupt aquatic biological systems due to their persistence and high bioaccumulation potential, causing structural damage and inflammatory responses. PS-MPs also act as metabolic disruptors, affecting glucose metabolism and insulin signaling, although the mechanisms underlying these effects remain unclear. In this study, grass carp were exposed to 100 μg/L and 400 μg/L of polystyrene MPs for 30 days. Histopathological analysis showed the shortening of intestinal villi, vacuolization, and inflammatory infiltration. Antioxidant enzyme activities (SOD and CAT) were reduced, while the presence of tissue damage markers (GPT and GOT) was elevated, suggesting a biphasic oxidative stress response. Transcriptomic analysis revealed downregulation of genes related to metabolism and insulin signaling, especially at 400 μg/L. Gene set enrichment analysis (GSEA) highlighted pathways related to insulin resistance and type 2 diabetes, indicating the disruption of glucose metabolism. Microbiome analysis showed reduced diversity, expansion of Proteobacteria (opportunistic pathogens), and a decrease in beneficial bacteria like Bacillus. These shifts correlated with changes in the expression of key insulin signaling genes, emphasizing the role of host–microbiota interactions in metabolic imbalances. This study revealed that PS-MPs disrupt glucose metabolism and insulin signaling in grass carp through a combination of histological damage, oxidative stress, and microbiota dysbiosis.